Relationship between size of fish with the total number of ectoparasites (monogeneans) on Ictalurus nebulosus Lesueur, 1819 (catfish) from fish farm at Ranau, Sabah / Nur Deanna Kamislin - Kamislin, Nur Deanna (Faculty of Applied Sciences, Universiti Teknologi MARA Sabah, 2017)
Monegeneans are ectoparasites of fishes that can cause serious damage in the aquaculture industry. The aims of this study are to investigate the types of monogeneans species on catfish and to see the correlation of the size of the catfish with the total number of ectoparasites found. The weight and length of the catfish were recorded and be compared with the total number of ectoparasites found. A total of 180 catfish collected from two selected farm fish namely Kg. Marakau and Kg. Libang were analysed for monogenean infection. Scraping method was applied on the catfish dorsal side, lateral line and anal fin by using a clean scalpel. The preservation method was used by using 70% ethanol. The mucus obtained was smeared on the clean glass slide and drops of 70% ethanol were added on the mucus before being observed by using a compound microscope. 10X until 40X magnification level was used for parasite identification. Physical parameter of the water quality was recorded by using the multiparameter YSI and pH meter. The results showed that only 5 types of monogeneans species were identified which are Capsalidae sp., Gyrodactylus sp., Dactylogyrus sp., Diclybothrium sp. and Paradiclybothrium sp. Most of the ectoparasites found were on the lateral line of the body of the catfish. This is because the lateral line on the catfish body surface holds a greater and wider surface area than the surface area for dorsal side and anal fin. The correlation between the size of the sample of this study versus the total number of ectoparasite shows negative relationship (r = - 0.440, p < 0.05). The smaller size fishes were more subjected to ectoparasite infection than the bigger one. This means that, the higher the size of the fish, the lower the total number of ectoparasites found on the fish. This might be because smaller catfish have a longer generation time to prevent the parasitic invasion and their immune system is not strongly developed yet.